2000
DOI: 10.1162/089892900564073
|View full text |Cite
|
Sign up to set email alerts
|

Attention Mechanisms in Visual Search—An fMRI Study

Abstract: The human visual system is usually confronted with many different objects at a time, with only some of them reaching consciousness. Reaction-time studies have revealed two different strategies by which objects are selected for further processing: an automatic, efficient search process, and a conscious, so-called inefficient search [Treisman, A. (1991). Search, similarity, and integration of features between and within dimensions. Journal of Experimental Psychology: Human Perception and Performance, 17, 652--67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
91
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 68 publications
17
91
1
2
Order By: Relevance
“…AD is associated with multi-focal pathological changes affecting many areas of visual processing [5,22,25] which may therefore affect many more aspects of visual function in addition to those related to the attention-related aspects of visual search. For example, recent fMRI data [24] do not clearly point to a dissociation between conjunction and single-feature search in visual cortex but do reveal differential activity in relation to the solution of the "binding problem". Thus, the differences found in our study may relate to aspects of vision not particularly related to visual search, but rather to "binding" difficulties or a failure of inhibition of responses to heterogeneous distractors.…”
Section: Discussionmentioning
confidence: 99%
“…AD is associated with multi-focal pathological changes affecting many areas of visual processing [5,22,25] which may therefore affect many more aspects of visual function in addition to those related to the attention-related aspects of visual search. For example, recent fMRI data [24] do not clearly point to a dissociation between conjunction and single-feature search in visual cortex but do reveal differential activity in relation to the solution of the "binding problem". Thus, the differences found in our study may relate to aspects of vision not particularly related to visual search, but rather to "binding" difficulties or a failure of inhibition of responses to heterogeneous distractors.…”
Section: Discussionmentioning
confidence: 99%
“…Both neuroimaging in humans (30) and single-unit recordings in monkeys (31) have revealed that the PPC subregions controlling spatial selection are also implicated in the selection of nonspatial features, suggesting that the involvement of the PPC in the visual search may not be binding-specific but rather reflect more general attention mechanisms. Furthermore, Leonards et al (32) and Donner et al (33) also reported PPC activations during the feature search task. Therefore, it was considered that the PPC plays a key role in the spatial perception and attention during visual search task.…”
Section: Disscussionmentioning
confidence: 94%
“…D'une façon générale, cette région occupe probablement une place importante dans la supervision des actions à exécuter. Une autre région, juste en avant du COF dorsomédian, dans le sillon frontal supérieur, intervient dans la mémoire spatiale à court terme [14,15].…”
Section: Saccades Volontaires Et Mémoire De Travail Spatialeunclassified
“…Ainsi, S.A. Brandt et al [19] L'imagerie fonctionnelle a permis d'explorer l'activité corticale mise en jeu lorsqu'on demande à des sujets de reproduire de mémoire une séquence qu'ils viennent d'effectuer de façon visuellement guidée [20][21][22][23]. En plus du réseau cortical impliqué dans le contrôle des saccades simples, les séquences de saccades activent un circuit composé principalement du précuneus, d'une région située dans le sillon intrapariétal, d'une région antérieure au COS et d'une région antérieure au COF, située dans le sillon frontal supérieur, qui correspond à un foyer déjà impliqué dans la mémoire spatiale à court terme (voir plus haut) [14] ou dans l'exploration spatiale [15]. Ces régions seraient donc activées spécifiquement dans l'exécution volontaire de séquences de saccades mémorisées, mais pas dans l'exécution de saccades simples (Figure 3).…”
Section: Contrôle Cortical Des Séquences De Saccadesunclassified